Progress of soft-x-ray absorption endstation for environmental samples - Wongjamras,A. (Elsevier BV, 2015)
A new endstation was developed at beamline 9.3.1 of the Advanced Light Source (ALS), Berkeley, CA, USA, to perform x-ray absorption experiments with soft x-rays on environmental samples such as liquid and hydroscopic solid samples at atmospheric pressure. The sample stage is separated from the vacuum of the beamline by a thin beryllium (Be) window which is 0.05 mm thick and 0.64 cm in diameter. A Si-photodiode is used to measure fluorescence from the sample. The experiments are conducted in an enclosure (mini-hutch) to protect users from x-ray radiation, to prevent ambient light from hitting the detector, and to allow running experiments with a background of another gas rather than air. Here we report on fluorescent-mode x-ray-absorption measurement at the chlorine K-edge of KCl and CCl3F in liquid and solid phases, illustrating the capabilities of the instrument and the technique. © 2011 Published by Elsevier Ltd.